Pengaruh Switching Cost Terhadap Customer Behavioral Loyalty dan Attitudinal Loyalty Pada Pelanggan Pre-Paid GSM Perusahaan Telekomunikasi di Kota Denpasar - Permana, I Gede Gilang; Giantari, I Gusti Ayu Ketut (E-Jurnal Manajemen; Vol 3 No 8 (2014), 2014)
Research to test and analyse influence of cost switching to loyalty behavioral customer and of attitudinal loyalty. Research responder amount to 150 one who use GSM prabayar provider. Intake of sampel use method of is non sampling probability specially sampling purposive. Research hypothesis tested to use technique analyse Structural Equation Modelling (SEM) with AMOS software 16.0. Result of analysis indicate that cost switching have an effect on positive and signifikan to loyalty behavioral customer and of attitudinal loyalty. Its meaning of excelsior of is expense of changing over consumer to other provider hence behavioral excelsior of attitude and loyalitas of loyalitas consumer at usage of GSM provider. Practical Implication to company of telecommunications specially at GSM prabayar provider is ever take care of and improve loyalitas usage of product, to be can maintain its cutomer, and anticipate all competitor which continue to have order to face emulation. Keyword : switching cost, customer behavioral loyalty, and attitudinal loyalty